THE USE OF HUMAN CHIP IMPLANTS FROM THE HADITH PERSPECTIVE - Fharadillah, Vira; Ghifari, Muhammad; Ash, Abil (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
The advancement of chip implant technology in humans has introduced profound transformations across multiple sectors, particularly in healthcare, security, and digital finance. These microelectronic devices, embedded within the human body, serve various functions ranging from medical monitoring and identification to real-time control of digital systems. In medical contexts, chip implants have demonstrated potential in managing chronic illnesses and streamlining access to patient health records. However, their integration into human life also provokes ethical and theological debates, especially within Islamic discourse. This study explores the Islamic ethical framework—focusing on the hadith of Prophet Muhammad Pbuh. —in evaluating the permissibility of chip implants. Employing a qualitative literature review, this research analyzes classical hadith texts alongside contemporary Islamic scholarship, fatwas, and bioethical debates. The study finds that while chip implants are not directly addressed in hadith, foundational Islamic legal principles such as lā ḍarar wa lāḍirār (no harm and no reciprocating harm), ḥifẓ al-nafs (protection of life), and privacy preservation provide normative guidelines. From this perspective, chip implants for urgent medical purposes are conditionally permissible, whereas their use for luxury, surveillance, or non-essential purposes may contravene Islamic ethical standards. This research contributes to contemporary Islamic bioethics by offering a hadith-based framework for navigating emerging biomedical technologies.[Kemajuan teknologi implan chip pada manusia telah membawa perubahan besar di berbagai bidang, khususnya dalam layanan kesehatan, keamanan, dan transaksi keuangan digital. Perangkat mikroelektronik ini, yang ditanamkan ke dalam tubuh manusia, memiliki berbagai fungsi mulai dari pemantauan medis dan identifikasi hingga pengendalian sistem digital secara real-time. Dalam konteks medis, implan chip menunjukkan potensi dalam menangani penyakit kronis serta mempermudah akses cepat terhadap data kesehatan pasien. Namun, integrasi teknologi ini dalam kehidupan manusia juga menimbulkan perdebatan etis dan teologis, terutama dalam wacana Islam. Studi ini mengkaji kerangka etika Islam—dengan fokus pada hadis Nabi Muhammad Saw. —dalam menilai kebolehan penggunaan implan chip. Dengan menggunakan metode kajian literatur kualitatif, penelitian ini menganalisis teks-teks hadis klasik bersama literatur keislaman kontemporer, fatwa, dan perdebatan bioetika. Hasil penelitian menunjukkan bahwa meskipun implan chip tidak secara eksplisit dibahas dalam hadis, prinsip-prinsip dasar hukum Islam seperti lā ḍarar wa lāḍirār (tidak boleh membahayakan diri sendiri maupun orang lain), ḥifẓ al-nafs (perlindungan jiwa), dan perlindungan privasi memberikan pedoman normatif. Dari sudut pandang ini, penggunaan implan chip untuk keperluan medis yang mendesak dapat dibolehkan secara syar’i, sedangkan penggunaannya untuk tujuan non-medis, kemewahan, atau yang berpotensi melanggar privasi dan membahayakan, dinilai bertentangan dengan standar etika Islam. Penelitian ini berkontribusi pada wacana bioetika Islam kontemporer dengan menawarkan kerangka etis berbasis hadis untuk menyikapi kemajuan teknologi biomedis.]